n(n-1)(n-2)(n-3)-84=0

Simple and best practice solution for n(n-1)(n-2)(n-3)-84=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n(n-1)(n-2)(n-3)-84=0 equation:


Simplifying
n(n + -1)(n + -2)(n + -3) + -84 = 0

Reorder the terms:
n(-1 + n)(n + -2)(n + -3) + -84 = 0

Reorder the terms:
n(-1 + n)(-2 + n)(n + -3) + -84 = 0

Reorder the terms:
n(-1 + n)(-2 + n)(-3 + n) + -84 = 0

Multiply (-1 + n) * (-2 + n)
n(-1(-2 + n) + n(-2 + n))(-3 + n) + -84 = 0
n((-2 * -1 + n * -1) + n(-2 + n))(-3 + n) + -84 = 0
n((2 + -1n) + n(-2 + n))(-3 + n) + -84 = 0
n(2 + -1n + (-2 * n + n * n))(-3 + n) + -84 = 0
n(2 + -1n + (-2n + n2))(-3 + n) + -84 = 0

Combine like terms: -1n + -2n = -3n
n(2 + -3n + n2)(-3 + n) + -84 = 0

Multiply (2 + -3n + n2) * (-3 + n)
n(2(-3 + n) + -3n * (-3 + n) + n2(-3 + n)) + -84 = 0
n((-3 * 2 + n * 2) + -3n * (-3 + n) + n2(-3 + n)) + -84 = 0
n((-6 + 2n) + -3n * (-3 + n) + n2(-3 + n)) + -84 = 0
n(-6 + 2n + (-3 * -3n + n * -3n) + n2(-3 + n)) + -84 = 0
n(-6 + 2n + (9n + -3n2) + n2(-3 + n)) + -84 = 0
n(-6 + 2n + 9n + -3n2 + (-3 * n2 + n * n2)) + -84 = 0
n(-6 + 2n + 9n + -3n2 + (-3n2 + n3)) + -84 = 0

Combine like terms: 2n + 9n = 11n
n(-6 + 11n + -3n2 + -3n2 + n3) + -84 = 0

Combine like terms: -3n2 + -3n2 = -6n2
n(-6 + 11n + -6n2 + n3) + -84 = 0
(-6 * n + 11n * n + -6n2 * n + n3 * n) + -84 = 0
(-6n + 11n2 + -6n3 + n4) + -84 = 0

Reorder the terms:
-84 + -6n + 11n2 + -6n3 + n4 = 0

Solving
-84 + -6n + 11n2 + -6n3 + n4 = 0

Solving for variable 'n'.

The solution to this equation could not be determined.

See similar equations:

| y^4+26y^3+169y^2-900=0 | | h=-5 | | 15+8x=45+6x | | 11-6n=29 | | (3k+5)(-k)= | | 3(4x-4)+52=6x+4 | | 5x+1=6x+17 | | 3x+52=80 | | 2015=101b+19a | | 3c-7=-3+1 | | 47=47-8(5-1w) | | 2y=3y+19 | | 4x-2=2x+x+4 | | 1v+1=1v-6 | | 4(8+m)= | | -8+x+6=2x+x | | A(w-3)+5=3(w-1) | | 6r-1+6=6r | | 8x^2-16x-80=1 | | -5-(15y-1)=2(17-16)-y | | -8.0a-8=0.2a | | 3x+4+4x+6x-11+5x-7=85 | | -6x-4=-52 | | 90=4y+10 | | 5x^2-16x-340=0 | | 8-w=8 | | h=81.688+2.392*50.1 | | 3(6+5y)= | | a^2-169=0 | | 10x+1=-9 | | 8senx-3=0 | | F(t)=-16t^2+45t+6 |

Equations solver categories